67.2k views
0 votes
Which equation is correctly rewritten to solve for x? -qx+p=r

2 Answers

0 votes

-q(x) + p = r

-q(x) = r - p

x = -r/q + p/q

Hope this helps! ;)

User Mirza
by
5.8k points
2 votes

Answer: x =
(p - r)/(q)

Explanation:

From the question -qx + p =r

To solve for x, we make x subject of the formula.

First we need to subtract p from both-side of the equation

-qx + p -p = r -p

The equation becomes

-qx = r - p

We want to make the left hand side of the equation positive, so we simply multiply through by a negative sign (-)

The our equation becomes

qx = -r + p

We can rearrange the equation, hence;

qx = p - r

Divide both-side of the equation by q


(qx)/(q) = (p - r)/(q)

(On the left hand side of the equation, the q numerator will cancel the q denominator, leaving us with only x)

x =
(p - r)/(q)

User Seabizkit
by
5.8k points